(untitled) (The Review of Diabetic Studies, 2025)
The rising burden of chronic diseases has placed preventive and family medicine at the center of health system reform, yet most delivery models remain physician- and nurse-centric, limiting the contributions of allied health professionals. This study examined the role of radiology, respiratory therapy, and health informatics, in collaboration with nursing and health assistants, in enhancing preventive care delivery. A convergent mixed-methods design was employed across six family medicine clinics, three hospitals, and four primary healthcare centers. Quantitative data were collected from 310 participants using validated questionnaires and electronic medical record (EMR) audits, while qualitative insights were drawn from 24 semi-structured interviews with senior staff. Survey reliability was high (Cronbach’s alpha > 0.85 across all constructs). Results indicated that interdisciplinary collaboration was positively associated with screening completion rates, early-stage disease detection, and patient navigation efficiency. SmartPLS modeling confirmed significant path coefficients between collaboration, EMR utilization, and preventive outcomes, while thematic analysis emphasized the importance of role clarity, structured reporting, and standing orders in sustaining efficiency gains. Findings align with international evidence that multicomponent, team-based interventions improve preventive processes, though capacity strain and role overlap remain challenges. Policy implications include incentivizing team-based screening bundles, developing interoperable data systems, and expanding training pathways for allied health integration in primary care. In conclusion, embedding radiology, respiratory therapy, and informatics within family medicine transforms fragmented preventive tasks into a coordinated system of care, offering a scalable framework for health ministries seeking to enhance equity, efficiency, and long-term population health outcomes.